2014
DOI: 10.1007/s13277-014-1867-3
|View full text |Cite
|
Sign up to set email alerts
|

Human IP10-scFv and DC-induced CTL synergistically inhibit the growth of glioma in a xenograft model

Abstract: The epidermal growth factor receptor (EGFR) mutant of EGFRvIII is highly expressed in glioma cells, and the EGFRvIII-specific dendritic cell (DC)-induced tumor antigen-specific CD8+ cytotoxic T lymphocytes (CTLs) may hold promise in cancer immunotherapy. Interferon (IFN)-γ-inducible protein (IP)-10 (IP-10) is a potent inhibitor of angiogenesis and can recruit CXCR3+ T cells, including CD8+ T cells, which are important for the control of tumor growth. In this study, we assessed if the combination of IP10-EGFRvI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…This analysis showed that CXCL9 production was significantly induced in an IFNg-dependent manner following therapy both at the transcriptional and protein level and that the production of CXCR3 ligands was critical for therapeutic efficacy. The requirement for the CXCL9:CXCR3 axis for the therapeutic efficacy of these immunotherapeutic treatments is consistent with previous data indicating that CXCL9/CXCL10:CXCR3 interactions govern immune cell infiltration into tumors prior to therapy (47) and following chemotherapy (10,48,49), IL2 treatment (50,51), adoptive cellular therapy (12,52,53), bispecific antibodies (54), and that CXCR3 À/À mice fail to elicit effective antitumor immune responses postvaccination and anti-PD-1 (55). These studies have shown that CXCL9 and CXCL10 can modulate antitumor immune responses evoked following several therapeutic approaches.…”
Section: Discussionsupporting
confidence: 89%
“…This analysis showed that CXCL9 production was significantly induced in an IFNg-dependent manner following therapy both at the transcriptional and protein level and that the production of CXCR3 ligands was critical for therapeutic efficacy. The requirement for the CXCL9:CXCR3 axis for the therapeutic efficacy of these immunotherapeutic treatments is consistent with previous data indicating that CXCL9/CXCL10:CXCR3 interactions govern immune cell infiltration into tumors prior to therapy (47) and following chemotherapy (10,48,49), IL2 treatment (50,51), adoptive cellular therapy (12,52,53), bispecific antibodies (54), and that CXCR3 À/À mice fail to elicit effective antitumor immune responses postvaccination and anti-PD-1 (55). These studies have shown that CXCL9 and CXCL10 can modulate antitumor immune responses evoked following several therapeutic approaches.…”
Section: Discussionsupporting
confidence: 89%
“…[72] Furthermore, a novel CXCL10-EGFRvIII fusion protein (IP10-scFv) with CTLs administration succeeded to induce tumor infiltrating lymphocytes and prolong survival, using a glioma mouse model. [73, 74] Since CXCL11 contributes to inducing Treg migration or promoting Tr1 and Th2 cells polarization, CXCL11-dependent therapy may be controversial as a new target for cancer therapy. In a mesothelioma mouse model, a tumor-selective oncolytic vaccinia virus with CXCL11 reportedly enhanced tumor-infiltrating CTLs and NK cells, but not CD4+ T cells, and prolonged survival.…”
Section: Cxcl9 Cxcl10 Cxcl11/cxcr3 Axis a Target For Cancer Treatmentmentioning
confidence: 99%
“…They can act as a synergistic factor to promote T cell activation and break down the immune tolerance of tumors. 9 They have chemotaxis and activation effects on monocytes, lymphocytes and neutrophils. 15,16 Chemokines are highly homologous and can be classified into C, CC, CXC and CX3C subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…IP10 can act as a synergistic factor to promote T cell activation and break down the immune tolerance of tumors. 9 It can enhance the chemotaxis and activation of monocyte macrophages, T cells and B cells, subsequently promoting the secretion of various cytokines to inhibit tumor growth. [9][10][11][12] It plays an important role in many diseases such as cancer, viral hepatitis, graft rejection and tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation